A checklist of the Medusae (Hydrozoa, Scyphozoa and Cubozoa) of Mexico - Segura-Puertas, Lourdes; Suárez-Morales, Eduardo; Celis, Laura (Zootaxa, 2003)
A list of 169 medusae species in 45 families recorded in Mexican waters is presented for the first time. 86 species (50.8%) were found in the Pacific Ocean, 75 species (44.3%) in the Gulf of Mexico, and 88 (52%) in the Mexican Caribbean Sea. Only 17 species (10%) were common to the three regions. The superclass Hydrozoa, the most diverse one, is represented by 151 species (89%), the Scyphozoa by 16 species (9.5%) and the Cubozoa by 3 (1.8%). Among the Hydrozoa, up to 6 new species have been described from Mexican waters. It is expected that the number of species will grow as surveys that include the hydroid stages and their laboratory-released medusae, as well as benthic and deep-living medusofauna are undertaken in both the Atlantic and the Pacific coasts of Mexico.